Cost-analysis and cost-effectiveness of physical activity interventions in brazilian primary health care: A randomised feasibility study - Papini, Camila Bosquiero; de Campos, Leonardo [UNESP]; Nakamura, Priscila Missaki; de Brito, Bruna Thaís Gomes; Kokubun, Eduardo [UNESP] (FapUNIFESP (SciELO), 2021)
Physical exercise programs have been carried out in primary health care in Brazil and have provided good results in terms of effective-ness, their economic contribution has not been investigated yet. The aim of the study is to verify the feasibility of brief counseling physical activity intervention and to compare its economic cost and cost-effectiveness with supervised physical exercise intervention in primary care. A multi-arm parallel feasibility trial, with equal randomization [1:1:1] was conducted in Basic Health Units in Brazil. 61 participants were randomized in Brief Counseling Intervention (BCI), Supervised Physical Exercise Intervention (SPEI) and Control Group (CG). Interventions lasted one year. The BCI is more economical than the SPEI, costing around 50% less in the economic comparisons (session cost, annual cost and cost per participant annually). At leisure time, the cost to move one person to the physically active category at 12 months is estimated in R$369.00 for BCI and R$426.21 for the SPEI. The Incremental Cost-effectiveness Ratio (ICER) is R$310.32. The BCI is feasible and more economic, however, the cost effective is not that different. Thus, it is strongly recommended that the two interventions be offered at primary care in Brazil.
Análise de custo e custo-efetividade de intervenções de atividade física na atenção primária à saúde no brasil: Um estudo de viabilidade randomizado
Keywords: Brief counseling; Physical exercise; Public health